2018
DOI: 10.2147/ccid.s155023
|View full text |Cite
|
Sign up to set email alerts
|

A comparative trial of ice application versus EMLA cream in alleviation of pain during botulinum toxin injections for palmar hyperhidrosis

Abstract: BackgroundBotulinum toxin is a safe and effective therapy for palmar hyperhidrosis, but the associated pain from injections limits the usefulness of this method of treatment.PurposeTo evaluate the efficacy of Eutectic Mixture of Local Anesthetics (EMLA) cream versus ice application in alleviation of pain during botulinum toxin injections for palmar hyperhidrosis.MethodsIn this prospective study, 23 patients underwent palm Botox injections to treat their excessive sweating. In each patient, EMLA cream was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, when ice is used, one study has reported that it resulted in a decrease in discomfort for the patients. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, when ice is used, one study has reported that it resulted in a decrease in discomfort for the patients. 19…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, when ice is used, one study has reported that it resulted in a decrease in discomfort for the patients. 19 Honey is a natural substance used in dentistry for the prevention of caries, treating gingivitis, and treating receding gingiva. 20 In our study, we used a natural sweet-tasting solution such as honey to assess its effect on pain experienced by the patients in administrating dental injections.…”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to a 40% to 50% reduction in pain with ice over EMLA. 46 Another cooling method uses dichlorotetrafluoroethane. In a self-controlled study, 40 patients with palmar HH had their left hand pretreated with dichlorotetrafluoroethane, whereas the right hand was pretreated with an ice pack.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the ethyl chloride spray was more effective than EMLA cream in reducing pain during neurotoxin injections in the forehead [122]. Another series of patients receiving botulinum toxin injections for palmar hyperhidrosis showed the superiority of ice packs over EMLA cream in reducing pain [123]. In contrast, Elibol et al [124] found that both EMLA cream and ice gel pack significantly reduce pain when injecting periocular neurotoxin, but there was no difference between ice and EMLA.…”
Section: Pain Management In Dermatologic Proceduresmentioning
confidence: 99%